2014
DOI: 10.1136/emermed-2014-203689
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for chest drain insertion may not prevent damage to abdominal viscera

Abstract: The results suggest these guidelines may result in insertion of chest drains below the fifth intercostal space, potentially risking injury to subdiaphragmatic structures. Peripheral nerves of the lateral thoracic wall appear safe from incisions 1 cm anterior to MAL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…This aims to protect important neurovascular bundles of the thoracic wall and achieve an acceptable cosmetic result, while avoiding the thickest part of the thoracic wall musculature 5. Our previous investigation in cadavers found a site 1 cm anterior to the MAL to be the safest position to avoid the long thoracic nerve and lateral cutaneous branches of intercostal nerves 6. This supports recommendations by the ETC and the ATLS course.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…This aims to protect important neurovascular bundles of the thoracic wall and achieve an acceptable cosmetic result, while avoiding the thickest part of the thoracic wall musculature 5. Our previous investigation in cadavers found a site 1 cm anterior to the MAL to be the safest position to avoid the long thoracic nerve and lateral cutaneous branches of intercostal nerves 6. This supports recommendations by the ETC and the ATLS course.…”
Section: Introductionsupporting
confidence: 60%
“…We have previously demonstrated that a site 1 cm anterior to the MAL avoids the long thoracic nerve and lateral cutaneous branches of intercostal nerves 6. The current data suggest that the tested methods often identify a safe site for chest drain insertion, if it is assumed that the fifth intercostal space is the lowest safe space on the lateral chest wall, although the same space is not reproducibly found.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Several commonly used guidelines describe landmark-based palpation techniques for ICD placement including the British Thoracic Society (BTS), the Advanced Trauma Life Support (ATLS) and the European Trauma Course (ETC) methods [10] , [11] , [12] . The BTS guidelines refer to the ‘triangle of safety’ as the appropriate area for ICD insertion.…”
Section: Introductionmentioning
confidence: 99%
“…This reinforces previous conclusions that current education may play an important role, with popular guidelines of the BTS, ATLS and ETC risking inferior placement of chest drains. 10 In the setting of trauma, 41% of TTs have been reported to be placed outside the triangle of safety, with most being too low. 11 Complication rates are low, but noted to be highest when the TT is performed in the emergency department (ED), 12 and inadequate training of all physicians dealing with trauma care was associated with the high morbidity rates of improper tube placement.…”
Section: Introductionmentioning
confidence: 99%